Factors of administrative corruption and the degree of its spread in the Algerian sports administration - bourenan khalil (sports creativity, 2025)
The study aimed to shed light on the main factors of administrative orruption and the degree of prevalence in sports management, and in order to achieve the goal was to follow the descriptive analytical approach, based on the scale of corruption of Professor d. Mohamed djamal Aali, and the scale was distributed to a group of workers in the Directorate of Youth and Sports randomly number of 49 workers, and after conducting the study procedures were reached a set of results, the most notable of which are: - Economic and social factors are one of the factors of the spread of administrative corruption in the Directorate of Youth and Sports in M'sila and this is largely, the most prominent of these factors (poor value of rewards and incentives for work requirements, lack of attention to religious and moral education). - Failure to define responsibilities and competencies, weak system of control and performance evaluation, one of the most important administrative factors in the spread of corruption in the Directorate of Youth and Sports. - Psychological factors of administrators contribute to a medium degree in the spread of corruption in the Directorate of Youth and Sports of the State of M'sila